Modification of Rubberwood Fibre by Graft Copolymerisation and its Application As Ion Exchanger and Filler in Polypropylene Composite - Abu-Ilaiwi, Faraj Ahmad (2004)
Graft copolymerisation of vinyl monomers such as poly(methyl acrylate) (PMA), poly(methyl methacrylate) (PMMA), and polyacrylonitrile (PAN) onto rubberwood fibre (RWF) was carried out by a free radical initiation. Hydrogen peroxide and ferrous ion were used as an initiator system to graft PMA and PMMA onto RWF, while potassium permanganate was used to graft PAN onto RWF. Effect of the reaction parameters (reaction temperature and reaction period, as well as hydrogen peroxide, ferrous ammonium sulphate, potassium permanganate, and monomer concentrations) on the percentage of grafting was investigated. The grafting percentage showed dependence on the initiator, Fe2+ and monomer concentrations, as well as the reaction temperature and reaction period. High percentage of grafting was achieved when the optimum reaction conditions were used. Optimum temperature of the polymerisation of PMA onto rubberwood fibre was found to be about 55 ºC for the reaction period 120 minutes. They were 60 ºC and 60 minutes for PMMA while they were 70 ºC and 180 minutes for PAN. Optimum concentration of H2O2 was 0.02 M and the amounts of Fe2+ 0.26 mmol when 0.05 mole of MA were used. When 2.36×10-2 moles of MMA were used, the concentration of H2O2 and amount of Fe2+ were 0.03 M and 0.26 mmol, respectively. PMA and PMMA homopolymers were removed from the graft copolymers by Soxhlet extraction using acetone. Optimum reaction conditions for grafting of PAN onto RWF were as follows: monomer amount; 0.18 mole, initiator amount; 4.0 mmol, nitric acid concentration; 0.2 M. PAN as homopolymer was removed from grafted product by DMF. The presence of PMA, PMMA and PAN on the fibre was confirmed by FTIR spectroscopy and gravimetric analysis. PAN grafted rubberwood fibre was converted to poly(amidoxime) ion exchange resin in order to remove heavy metal ions from aqueous solutions. The cation-exchange resin exists predominantly in the syn-hydroxyamino form. The water uptake by the resin was about 31 g/g dry resin, and hydrogen capacity was 3.6 mmol/g. The absorption capacity for different metal ions from wastewater was determined at different pH’s from 1 to 6. The prepared chelating ion exchanger gives highest adsorption capacity for Cu2+, which was 3.83 mmol/g, followed by Cd2+, Fe3+, Pb2+, Ni2+ and Co2+, respectively. Poly(amidoxime) ion exchanger resin was also used to separate cobalt and nickel ions from copper ion by using column technique. PMA grafted RWF was converted to poly(hydroxamic acid) ion exchanger resin. Adsorption of metal ions was studied at different pH’s and it showed that the highest adsorption was for lead ion. The results showed that the absorption capacity depended on the solution pH. FTIR spectroscopy was used to confirm the conversion of grafted fibre to ion exchanger resin. The percentage of moisture absorbed by the grafted products decreased depending on the grafted polymer. The moisture content in the fibre was reduced from 6 to less than 1% when PMA was grafted onto RWF. Activation energies (Ea) of RWF and its grafted copolymers were analysed by thermogravimetric analysis (TGA) and dynamic derivatives of the thermogravimetric (DTG). It was found that RWF and RWF-g-PMMA were degraded by one-step decomposition and their Ea are 91 and 96 KJ/mole respectively. On the other hand, RWF-g-PMA degraded by two steps while RWF-PAN degraded by three steps. The highest Ea of RWF-g-PMA was 199 KJ/mole of the second step but it was 200 KJ/mole for RWF-g-PAN at the first step. Temperature of first steps degradation of RWF and its grafted copolymers were as follows: RWF; 352 ˚C, RWF-g-PMA; 362 ˚C, RWF-g-PMMA; 370 ˚C, and RWF-g-PAN; 354 ˚C. As an application of RWF-g-PMMA copolymer, it was used with RWF to prepare fibre/polypropylene composite. It was found that the tensile strength decreased with increasing of the fibre loading. Tensile strength and modulus were improved when 20% of grafted fibre was used with RWF in preparation of composite when it was radiated by electron beam radiation. However, increasing the fibre loading increased tensile and flexural moduli. On the other hand, toughness of the composite was improved when grafted RWF was used as a filler of PP composite.